Developing communication skills in 21st century electric engineering students - Ponikarovska, Svitlana; Понікаровська, Світлана Володимирівна; Поникаровская, Светлана Владимировна (Харківський національний автомобільно-дорожній університет, 2019)
Communication skills are an essential component in the education of engineering students to facilitate not just students’ education but also to prepare them for their future careers. Various important communication skills required of modern engineers, such as foreign language skills, are discussed in this article, as well as multiple elements of communication skills training, such as oral, listening, written, visual, interdisciplinary and intercultural. The impact of emotional intelligence is also presented. Goal. The goal of the article is proving the idea that the classes of foreign language can be a combination of learning language and acquiring communication skills. Methodology. Methods of analysis, research and development of new solution were used. Results. In the result of the analysis it was proven that classes of English can develop not only the language skills but add to the overall development of personality, as well as enhance various kinds of communication skills necessary for the graduate of engineering (in particular, electrical engineering) specialties. Originality. Suggestions for communication skills development are made, including the one that communication skills be integrated in the curriculum, so as to reinforce student learning. Practical Value. The practical value of the work can be the ideas for improving communication tasks as well as development of the approach which includes both language learning and integration of engineering communication in the process of learning.
Розвиток комунікативних навичок у студентів електротехнічної спеціальності 21 століття
Развитие коммуникативных навыков у студентов электротехнической специальности 21 века
Keywords: communication; abilities; behavior; society; knowledge; international; комунікація; здібності; поведінка; суспільство; знання; міжнародний; коммуникация; способности; поведение; общество; знания; международный; 378.14; 10.30977/VEIT.2019.15.0.100